Gubernator - Warren, Robert Penn, 1905-1989 (Poznan : Rebis, 1999)
Polish translation of "All the king's men". A chilling political novel about southern politics and politicians circa 1947.
Translation of: All the king's men.
Keywords: Politicians -- Southern States -- Fiction; Political fiction